Race and repast : foodscapes in twentieth-century Southern literature - Niewiadomska-Flis, Urszula (Food and foodways (Fayetteville, Ark.), 2022)
"Race and Repast: Foodscapes in Twentieth-Century Southern Literature examines how race relations are expressed through struggles over the meaning of food and access to food in Southern literature. This innovative investigation offers new perspectives on the history of racial conflict in the South while illuminating how the very act of eating together allowed Southerners to cross race and class lines at a time of great strife"--